Fixed Orthodontic Retainers: A Review - Yasemin Kartal; Burçak Kaya (Turkish Journal of Orthodontics, 2019)

(untitled)
Orthodontic retention is defined as maintaining teeth in optimal aesthetic and functional position after treatment. Despite the necessity of retention phase and the factors influencing the stability of the teeth after orthodontic treatment was discussed by the orthodontist for a long time, it is accepted that a retention phase is essential for stability of orthodontic treatment results nowadays. Therefore, the application of a suitable retention method is important both for prevention of relapse after orthodontic treatment and for increasing patient satisfaction. Removable appliances had been used for many years for retention purposes. Later, fixed retainers were introduced to prevent relapse as having a number of advantages, such as better aesthetics, no need for patient cooperation, effectiveness, and suitability for lifelong retention. However, their need for precise bonding technique, fragility, and tendency to cause periodontal problems by weakening oral hygiene are some of their disadvantages.